Currency Evolution: A Comparative Study Between Central Bank Digital Currencies And Physical Currencies In Modern Monetary Systems - Indah Noviyanti; Ary Fakturrachman Aryansyah; Iza Guspian; Novita Herlissha (Universitas Bangka Belitung, 2024)
Technology and innovation are the keys used to unlock the impossible imagination to become possible to achieve the unforeseen goals of individuals and organizations. This study focuses on the role of an unprecedented phenomenon called central bank digital currency (CBDC) over physical currency. This study uses a descriptive research method with a quantitative approach. This study is a literature review study aimed at describing the phenomenon. This study assesses the role of CBDC based on three parameters such as features, perceived benefits and challenges of CBDC and Physical Currency. It also reveals that CBDC can replace the use of physical currency only depending on how people, businesses perceive the features, benefits (better allocation, accessibility, interest bearing, convertibility and reduced costs) and possible challenges (opposite of benefits) associated with CBDC compared to its counterpart.